A potential pathway for identifying hypertension among urban residents aged 60+ years in China: the role of health insurance - Dou, Yu; Guo, Hongmei; Liu, Sijun; Xu, Huiqing; Li, Fengli; Tao, Wanying; Jia, Shifen; Tian, Siyu; Deng, Tianrui; Xiong, Yaqing; Xu, Fei (Frontiers in Public Health, 2024)
Background Identification is the first step for treatment of hypertension. However, the awareness rate of hypertension was not high globally. This study aimed to examine the potential role of health insurance for early-identifying hypertension among urban older residents in China. Methods In this cross-sectional study, urban residents aged 60+ years were chosen from Nanjing municipality of China in 2018. The outcome measure was hypertension status (“no hypertension”, “diagnosed hypertension” or “un-diagnosed hypertension”). Independent variable was health insurance (“Urban Employee Basic Medical Insurance scheme, UEBMI” or “Urban Resident Basic Medical Insurance scheme, URBMI”). Logistic regression models were introduced to estimate odds ratio (OR) and 95% confidence interval (CI) to examine the association between health insurance and hypertension. Results Totally, 19742 participants completed the study. Among overall, URBMI and UEBMI participants, 47.2% (95%CI=46.5%, 47.9%), 38.4% (95%CI=37.3%, 39.6%) and 52.1% (95%CI=51.2%, 53.0%), separately, were diagnosed with hypertension, while the prevalence of un-diagnosed hypertension was 12.7% (95%CI=12.2%, 13.2%), 18.5% (95%CI=17.6%, 19.4%) and 9.6% (95%CI=9.1%, 10.1%), respectively. For overall participants, those with UEBMI were more likely to have hypertension identified (OR=1.20; 95%CI=1.11, 1.29) and at lower odds to experience un-diagnosed hypertension (OR=0.68; 95%CI=0.61, 0.76) compared to their counterparts with URBMI after control for potential confounders. Moreover, such associations of health insurance with diagnosed and un-diagnosed hypertension were also observed among participants stratified by age and gender. Conclusions Favorable health insurance may be a pathway for identifying hypertension among urban older residents in China. This study has important public health implications that hypertension may be identified early through favorable health insurance policies for older residents in China.